KEWENANGAN BADAN PENGAWAS DALAM MENCEGAH PELANGGARAN ADMINISTRATIF MELALUI SISTEM PEMERIKSAAN ACARA CEPAT PADA PUTUSAN PENGAWASAN PEMILU DI SUMUT - Muhammad Akbar Siregar; Mirza Nasution; Edy Ikhsan; Afnila Afnila (Law Jurnal, 2023)
ABSTRACTAct number 7 of 2017 on General Elections had established the existence and the role of The GeneralElection Supervisory Board not only function as election monitors, but to act as an institution tasked withresolving disputes over electoral processes, both participants in inter-election disputes and acrosscommittees for the public. In this study raised the issue of the legal power of The General ElectionSupervisory Board of North Sumatra Province No. 002/LP/PL/ADM/PROV/02.00/V/2019. The researchmethodology is juridically normative, in the research concluded that The General Election SupervisoryBoard of North Sumatra Province No. 002/LP/PL/ADM/PROV/02.00/V/2019 has permanent legal forcebecause the decision is not carried out legal efforts by The Election Commission of North SumatraProvince and The Election Commission of West Nias Regency so that the decision final and binding, sothat decisions which are was born of The General Election Supervisory Board has an executory nature.Keywords : General Elections, The General Election Supervisory Board, and Quick Event Check